Analisis Pengaruh Current Ratio, Debt To Equity Ratio dan Net Profit Margin Terhadap Perubahan Laba Pada Perusahaan Saham Syariah Sektor Perdagangan Jasa Investasi Yang Terdaftar Di Bursa Efek Indonesia - Vindi Paputungan (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2021)
This study aims to determine the effect of Current Ratio (CR), Debt To Equity Ratio (DER) and Net Profit Margin (NPM) either simultaneously or partially on changes in earnings in Islamic stock companies in the investment services trading sector listed on the Indonesian stock exchange. The research period starts from 2018-2019. The type of data used is secondary data. The population in this study amounted to 89 companies. The sample selection was carried out using purposive sampling method, in order to obtain a sample of 53 companies. Simultaneous test results (f test) show Current Ratio (CR), Debt to Equity Ratio (DER) and Net Profit Margin (NPM) simultaneously have a significant effect on earnings changes where the independent variable is only able to explain the independent variable by 38.6% as for the remaining 61.4% is explained by other variables. The partial test results (t test) show that the variable Current Ratio (CR) has a negative and significant effect on changes in earnings, while the Debt to Equity Ratio (DER) has no significant effect on changes in earnings and Net Profit Margin (NPM) has a positive and significant effect. to changes in earnings in Islamic stock companies in the investment services trading sector listed on the Indonesia Stock Exchange for the period 2018 - 2019